The effect of replacing fishmeal with Spirulina on microbial load in common carp Cyprinus carpio L - N.M. Abdulrahman (Iraqi Journal of Veterinary Sciences, 2013)
The use of blue green algae Spirulina in aquaculture has several potential advantages over the production of fish. This study was designed to investigate the effect of different replacement levels of fishmeal with Spirulina on microbial load of common carp Cyprinus carpio L., the trail was conducted for 105 days and for this purpose 200 fingerlings common carp. Mean initial weight was (32.7 g). The fish were acclimated to laboratory conditions and fed with control pellets (32% protein) prior to the feeding trials for 21 days. Five experimental diets were used and Spirulina replaced fishmeal protein from the standard diet at 0% (T1), 5% (T2), 10% (T3), 15% (T4) and 20% (T5) levels. Bacterial total account in rearing water and the bacterial total count in carp intestine for the third treatment was higher significantly as compared to other treatments, which is the conclusion of this study.